Carvacrol activated biopolymeric foam: An effective packaging system to control the development of spoilage and pathogenic bacteria on sliced pumpkin and melon. (June 2021) - Gaglio, Raimondo; Botta, Luigi; Garofalo, Giuliana; Miceli, Alessandro; Settanni, Luca; Lopresti, Francesco
Highlights: Mater-Bi (MB) activated with carvacrol showed antibacterial properties. Carvacrol (CRV) slightly increased the porosity of the foams. Carvacrol reduced the compressive elastic modulus and tensile elastic modulus. Carvacrol release occurred at 7% after 5 h and at 35.4 % after 900 h. MB/CRV inhibited the growth of P. poae and L. monocytogenes on melon and pumpkin. Abstract: A commercial biodegradable starch-based polymer (Mater-Bi) was activated with carvacrol to develop a biodegradable and compostable polymer to be used in food packaging. Based on previous tests, carvacrol was added at 20 % weight of foam. MB foams, with and without carvacrol, were tested for their morphological characteristics, mechanical tests and kinetics of carvacrol release under refrigerated storage conditions. Carvacrol slightly increased the porosity of the foams, induced a reduction of the compressive elastic modulus (Ecom ) of foamed MB from 6 to ∼ 3.4 MPa and a decrease of the tensile elastic modulus from ∼70 MPa to ∼16.5 MPa. Carvacrol release from the foam at 4 °C was almost 7% of the initially loaded amount at the fifth hour, while 35.4 % at the end of the test (900 h). MB containing carvacrol was active against several pathogenic and spoilage bacteria in vitro . Trays made of MB containing carvacrol were put in contact with meat, fish and vegetable food systems, artificially contaminated with Pseudomonas poae 4G558 and Listeria monocytogenes 13BO. No antimicrobial effect of MB foams was registered for ham and salmon trials, while a clear inhibitory effect of carvacrol activated MB foams was observed for contaminated melon and pumpkin in which both bacteria decreased of about 1 log cycle after 3 d and completely disappeared from the 7th d of refrigerated storage. This study provided evidences on the suitability of MB foams containing 20 % carvacrol as active packaging systems for vegetables even though it negatively affected their physicochemical parameters and overall quality.